2017
DOI: 10.1051/0004-6361/201731544
|View full text |Cite
|
Sign up to set email alerts
|

Gaiaand VLT astrometry of faint stars: Precision ofGaiaDR1 positions and updated VLT parallaxes of ultracool dwarfs

Abstract: Aims. We compared positions of the Gaia first data release (DR1) secondary data set at its faint limit with CCD positions of stars in 20 fields observed with the VLT/FORS2 camera. The FORS2 position uncertainties are smaller than one milli-arcsecond (mas) and allowed us to perform an independent verification of the DR1 astrometric precision. Methods. In the fields that we observed with FORS2, we projected the Gaia DR1 positions into the CCD plane, performed a polynomial fit between the two sets of matching sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…For targets near the Galactic plane, where a large number of reference stars is available, and 0.4 seeing, the initial estimates of Lazorenko & Lazorenko (2004) indicated an achievable astrometric accuracy of 0.01-0.06 mas for faint stars. With the Very Large Telescope (VLT) camera FORS2 (Appenzeller et al 1998) we demonstrated a single-epoch astrometric accuracy close to 0.1 mas for 15-20 mag stars and 0.6 atmospheric seeing (Lazorenko et al 2009;Sahlmann et al 2014;Lazorenko et al 2014;Lazorenko & Sahlmann 2017). This accuracy is sufficient to detect and characterize the orbits of Jupiter-mass companions to nearby ultracool dwarfs.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…For targets near the Galactic plane, where a large number of reference stars is available, and 0.4 seeing, the initial estimates of Lazorenko & Lazorenko (2004) indicated an achievable astrometric accuracy of 0.01-0.06 mas for faint stars. With the Very Large Telescope (VLT) camera FORS2 (Appenzeller et al 1998) we demonstrated a single-epoch astrometric accuracy close to 0.1 mas for 15-20 mag stars and 0.6 atmospheric seeing (Lazorenko et al 2009;Sahlmann et al 2014;Lazorenko et al 2014;Lazorenko & Sahlmann 2017). This accuracy is sufficient to detect and characterize the orbits of Jupiter-mass companions to nearby ultracool dwarfs.…”
Section: Introductionmentioning
confidence: 82%
“…This common star list was derived at the first identification between FORS2 and Gaia at the epoch nearest to the Gaia reference epoch T DR2 = 2015.5. The identification procedure was similar to that described in Lazorenko & Sahlmann (2017, where we used full bivariate polynomials of the maximum power n for the transformation between catalogs. We used stars in both chips for this transformation.…”
Section: Using Gaia Dr2 To Estimate the Chip Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…As explained in Lazorenko & Sahlmann (2017), the transformation was made only with stars imaged on the upper chip because the bottom CCD chip2 of FORS2 is rotated and shifted relative to the upper chip1, and the use of both chips leads to large residuals of about 50 mas. We tangent-plane projected the Gaia equatorial coordinates to the CCD plane at the point (1) known with about twice better internally consistent precision as compared to DR2 (but systematically offset from the absolute, see Sect.…”
Section: Transformation To the Dr1 Epochmentioning
confidence: 99%
“…Including additional epochs obtained in 2014 with FORS2, (Sahlmann & Lazorenko 2015) derived the relative (500.23 mas) and absolute parallax ̟ abs = 500.51 ± 0.11 mas of this system, obtained an upper mass limit for a potential third body of 2M Jup , and determined a mass ratio q = 0.78 ± 0.10 for the LUH 16 binary. After publication of Gaia Data Release 1 (DR1 Gaia Collaboration et al 2016b,a;Lindegren et al 2016), we updated the FORS2 distortion correction, which led to the updated values of 501.139 mas and ̟ abs = 501.419 ± 0.11 mas for the relative and absolute parallax, respectively (Lazorenko & Sahlmann 2017).…”
Section: Introductionmentioning
confidence: 99%